Campaniforme: chronology, pottery, and contexts of a long term phenomenon in the Portuguese Douro Basin - Sanches, Maria de Jesus (2018)
This paper discusses the Campaniforme, or Bell Beaker, phenomenon in the lower Douro river basin, Portugal (Northwestern Iberian Peninsula) focusing on pottery. It analyses the style and respective archaeological context of the ceramics as well as their geographic distribution and presents the absolute and relative chronology of about 50 sites. We highlight here four case studies and conclude that all styles are present classic Maritime (linear, herringbone), comb-geometric, Palmela/Ciempozuelos, AOC and mixed C/ZM styles and that these styles have grosso modo the same chronology, i.e., they are dated to at least as old as the second quarter of the 3rd millennium BC. Bell Beaker pottery continued to be used in the second half of the 3rd millennium BC in this region, making this phenomenon one of long duration. This paper also emphasizes the spatial segregation of the use of Bell Beaker ceramics and its relation to ritualized social practices which would have been connected with identity management, regional conflicts, or marriage alliance.